Impact of participatory design for drug-drug interaction alerts. A comparison study between two interfaces - Luna, Daniel Roberto (2016)
Decision support systems for alert drug-drug interactions have been shown as valid strategy to reduce medical error. Even so the use of these systems has not been as expected, probably due to the lack of a suitable design. This study compares two interfaces, one of them developed using participatory design techniques (based on user centered design processes). This work showed that the use of these techniques improves satisfaction, effectiveness and efficiency in an alert system for drug-drug interactions, a fact that was evident in specific situations such as the decrease of errors to meet the specified task, the time, the workload optimization and users overall satisfaction with the system.